Genetics of melanocytic nevi. (November 2015) - Roh, Mi Ryung; Eliades, Philip; Gupta, Sameer; Tsao, Hensin
Summary Melanocytic nevi are a benign clonal proliferation of cells expressing the melanocytic phenotype, with heterogeneous clinical and molecular characteristics. In this review, we discuss the genetics of nevi by salient nevi subtypes: congenital melanocytic nevi, acquired melanocytic nevi, blue nevi, and Spitz nevi. While the molecular etiology of nevi has been less thoroughly studied than melanoma, it is clear that nevi and melanoma share common driver mutations. Acquired melanocytic nevi harbor oncogenic mutations in BRAF, which is the predominant oncogene associated with melanoma. Congenital melanocytic nevi and blue nevi frequently harbor NRAS mutations and GNAQ mutations, respectively, while Spitz and atypical Spitz tumors often exhibit HRAS and kinase rearrangements. These initial 'driver' mutations are thought to trigger the establishment of benign nevi. After this initial phase of the cell proliferation, a senescence program is executed, causing termination of nevi growth. Only upon the emergence of additional tumorigenic alterations, which may provide an escape from oncogene‐induced senescence, can malignant progression occur. Here, we review the current literature on the pathobiology and genetics of nevi in the hope that additional studies of nevi promise to inform our understanding of the transition from benign neoplasm to malignancy.